A new approach to the analysis of pitch-positions in professional soccer - Konefal, M.; Chmura, P.; Zajac, T.; Chmura, J.; Kowalczuk, E.; Andrzejewski, M. (Journal of Human Kinetics, 2019)
The purpose of the study was to examine how various playing positions affected the number of (and percentage breakdowns for) physical and technical activities of soccer players in the Germany`s Bundesliga. A further objective was to identify and present features distinguishing between the activities of players within the Defender, Midfielder and Forward formations. The study sample comprised 4426 individual match observations of 473 soccer players competing in the Bundesliga during the 2016/2017 domestic season. Data from the Impire AG motion analysis system, and the so-called "heat maps" it supplies, revealed areas in which players spent most time during a match, with 22 different playing positions on the pitch identified in consequence. Players in the formation comprising Defenders did not differ significantly in relation to the number of accelerations, the number of shots or the percentage of duels won. Furthermore, there were no significant differences among Midfielders in regard to total distance covered, mean running speed, the number of accelerations, the number of duels and the percentage of duels won. Likewise, Forwards did not differ in distances covered at =24 km/h, average running speed, the number of sprints, the number of shots, the proportion of on-target passes, the number of duels, or the percentage share of duels won. Irrespective of the formation or position on the pitch, today`s game of soccer also pays great importance to the number of accelerations, as well as the number of duels engaged in, and their effectiveness.